Incidence of contrast induced nephropathy among patients undergoing coronary interventions - Ch Veerendra Dr. Ch Veerendra Ravi Kiran; Muralidhar G; Ravikanth K. R.; Jaya Chandra T (International Journal of Medical Research and Review, 2019)
Background: Contrast media (CM) used during diagnostic and therapeutic percutaneous procedures is eliminated by the kidneys. A study has been planned to find the adverse effects of contrast agents on renal system.Methods: This was a hospital based cross sectional study, conducted in the department of general medicine, GSL Medical College. Individuals >25 age, both gender with heamoglobin concentration of > 10mg/dl were included. Exclusion criteria was also followed. Iodixanol or iohexol was used, administered at the rate of 80 – 100 ml per participants. Blood samples were collected standard techniques before the procedure and 48 hours after the procedure for serum creatinine levels. Renal function was assessed by estimating creatinine clearance using the Cockcroft-gault formulae. As per national kidney foundation participants were divided in to 4 categories normal, mildly impaired, moderately impaired and severely impaired renal function; p<0.05 was considered as statistically significant.Results: Out of 80 study subjects, CIN was increased with age, identified in 37.9% diabetics, 48.3% smokers, 41.4% alcoholics; statistically there was no significant difference. In the normal category 34.5%, 41.4% in mild category, 24.1% in moderate renal dysfunction category developed CIN, association was statistically significant.Conclusions: With these findings we conclude that overall increase in the incidence of CIN with age and no influence of gender as well as conditions like diabetes and hypertension.